Awareness of the passage of time and self‐consciousness: What do meditators report?. Issue 1 (10th February 2019) - Droit‐Volet, Sylvie; Dambrun, Michaël
Abstract: What do humans mean when they say that time passes quickly or slowly? In this article, we try to respond to this question on the basis of our studies on the judgment of the passage of time and its links with the judgment of physical durations. The awareness of the passage of time when consciousness is altered by meditation is also discussed. A dissociation is then made among the "self‐time perspective, " the "self‐duration" (internal duration), and the "world‐duration" (external duration). A link is also established between the self‐time perspective and the "narrative self, " on one hand, and the self‐duration and the "minimal self, " on the other hand, that is confirmed in our qualitative analysis of testimonials of four meditators. The awareness of self‐duration is thus related to the awareness of the embodied self. When the sense of self is altered and the consciousness of the body is lower, then the subjective experience of internal time changes. However, the mechanisms allowing the disappearance of the self with the feeling of being outside time during meditation remains to be elucidated.